Geology and Alteration of East Pinolosian Area, Bolaang Mongondow, North Sulawesi Province - Mardain, Tober; Arifin, Yayu Indriati; Kasim, Muhamad; Rosadi, Dhani Rhamdani (BRIN Publishing, 2022)
Bolaang Mongondow is located on the Eastern North arm of Sulawesi. This area is a Neogene-aged magmatic arc composed of plutonic and volcanic rocks that indicate mineralization-bearing host rocks. The study aimed to determine the geological setting and alteration based on geological observations and geochemical analysis. The method used is geological mapping, followed by laboratory and studio data analysis. The lithology of this area is composed of andesite, diorite, and pyroclastic breccia units. Two main faults are the Northwest-Southeast trending dextral fault and the Northeast-Southwest trending sinistral fault, which causes hydrothermal mineral alteration. Mineral alteration in the study area is divided into several zones, including the Silicification Zone (massive silica + vuggy silica), Advance Argillic Zone (illite + alunite + dickite + halloysite + kaolinite), Argillic Zone (illite + montmorillonite + pyrophyllite), Prophyllitic Zone (chlorite + montmorillonite). The presence of mineral assemblages and alteration zones shows the characteristics of High Sulfide Epithermal deposits with the highest level of 0.47/ppm in the Advance Argillic Zone.